Religiosity and Trust in Islamic Banking in Pekanbaru City Indonesia - Iskamto, Dedi; Yapentra, Arhipen (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research is intended to examine the level of Religiosity towards trust in Islamic banking. This research was conducted in Pekanbaru City, Riau Province, Indonesia with a sample of 400 people. The research was conducted from May to August 2018. Indications of Religiosity are associated with the dimensions of the dimensions of religious practice, the dimensions of beliefs-creeds, the dimensions of religious knowledge, and the dimensions of practice ..From the results of the study obtained the value of the determinant coefficient (R Square) of 0.062. This means that the effect of Religiosity on trust in Islamic banks is 6.2% while the remaining 93.8% is influenced by other variables.Partial regression analysis between Religiustisa (X1) on Trust in Islamic Banks (Y) has a significant influence this can be seen from the results of data processing obtained that testing hypotheses with t test there is an t count of 5.120 means tcount> t table = 1.966 which means Religiosity significant effect on trust in Islamic banks.linear analysis From the results of the SPSS data, the regression equation is obtained as follows: Y = 26,939 + 0,263 X1